Family history of immune conditions and autism spectrum and developmental disorders: Findings from the study to explore early development. Issue 1 (10th August 2018) - Croen, Lisa A.; Qian, Yinge; Ashwood, Paul; Daniels, Julie L; Fallin, Daniele; Schendel, Diana; Schieve, Laura A.; Singer, Alison B.; Zerbo, Ousseny
Abstract : Numerous studies have reported immune system disturbances in individuals with autism and their family members; however, there is considerable variability in findings with respect to the specific immune conditions involved, their timing, and the family members affected and little understanding of variation by autism subphenotype. Using data from the Study to Explore Early Development (SEED), a multi‐site case‐control study of children born 2003–2006 in the United States, we examined the role of family history of autoimmune diseases, asthma, and allergies in autism spectrum disorder (ASD) as well as other developmental disorders (DD). We investigated maternal immune conditions during the pregnancy period, as well as lifetime history of these conditions in several family members (mother, father, siblings, and study child). Logistic regression analyses included 663 children with ASD, 984 children with DD, and 915 controls ascertained from the general population (POP). Maternal history of eczema/psoriasis and asthma was associated with a 20%–40% increased odds of both ASD and DD. Risk estimates varied by specific ASD subphenotypes in association with these exposures. In addition, children with ASD were more likely to have a history of psoriasis/eczema or allergies than POP controls. No association was observed for paternal history or family history of these immune conditions for either ASD or DD. These data support a link between maternal and child immune conditions and adverse neurodevelopmental outcomes, and further suggest that associations may differ by ASD phenotype of the child. Autism Research 2019, 12: 123–135 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Using data from a large multi‐site study in the US—the Study to Explore Early Development—we found that women with a history of eczema/psoriasis and asthma are more likely to have children with ASD or DD. In addition, children with ASD are more likely to have a history of psoriasis/eczema or allergies than typically developing children. These data support a link between maternal and child immune conditions and adverse neurodevelopmental outcomes.